Historical Dictionary of Competitive Swimming - Lohn, John (Rowman & Littlefield Publishers, 2010)
Swimming has been an Olympic sport since the inception of the Games, with the 100, 400, and 1500 freestyles being the original events along with the 100 freestyle for sailors. While the spirit of the sport remains the same, the technology and the competitive formats have advanced tremendously through the years. The number of events contested in competition has increased to the point where the program for a typical international meet, such as the World Championships or Olympics, produces a true reflection of the best swimmers over various distances and in different strokes. The Historical Dictionary of Competitive Swimming examines the sport of swimming since its inception as a competitive athletic event. This is done through a chronology, an introductory essay, a bibliography, and appendixes that detail Olympic and World Championships medal winners. The dictionary section has over 500 cross-referenced dictionary entries on individuals, major competitions, and there are also entries for each of the competitive strokes and countries that have enjoyed significant success in the sport.